Student worksheet: Persepsi dan performa akademik mahasiswa keperawatan - Indah Dwi Pratiwi; Risa Herlianita; Indri Wahyuningsih (Indonesian Health Science Journal, 2022)
Background: Students' perceptions of learning methods may be influenced by the diversity of students, educational facilities and equipment, their expectations, and other university circumstances. This study aims to identify or examine student perceptions about the use of learning media in the form of student worksheets, especially in the Emergency Nursing course, which is expected to see the optimization of learning. Methods: The design of this study was a descriptive observational study with a cross-sectional approach. The population in this study were 82 nursing students at a university in Malang, where respondents were asked to fill out a questionnaire. The data collected will be analyzed descriptively and analytically. Results: In this study, the results showed that the majority of students had a good perception (85.4%) about the use of student worksheets in Emergency Nursing courses, more than half of them had above-average academic performance (59.8%), and there was a significant relationship between students' perception of academic performance (p-value < 0.000). Conclusion: Improvements in the learning environment can improve student academic performance.